2010
DOI: 10.1038/gene.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin gene variability increases the risk for primary progressive multiple sclerosis in males

Abstract: Progranulin (GRN) gene variability has been analyzed in a sample of 354 patients with multiple sclerosis (MS) compared with 343 controls. No significant differences were observed, but by stratifying according to MS subtypes, a significant increased frequency of the rs2879096 TT genotype was found in primary progressive MS (PPMS) patients versus controls (16.0 vs 3.5%, P ¼ 0.023, odds ratio (OR) 5.2, 95% confidence interval (CI) 1.2-21.4). In addition, in PPMS, an association with the C allele of rs4792938 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…12 Here, for the first time, GRN variability has been associated with the prognosis in a large population, followed up for several years with detailed data on disability load (MSSS) and on relapses. Notably, serum levels in carriers of the rs9897526 and rs5848 variants are significantly lower than in non-carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Here, for the first time, GRN variability has been associated with the prognosis in a large population, followed up for several years with detailed data on disability load (MSSS) and on relapses. Notably, serum levels in carriers of the rs9897526 and rs5848 variants are significantly lower than in non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…All the assays were performed as described previously. 12 Serum isolation and determination of progranulin levels For serum isolation, whole blood samples were allowed to sit at room temperature for a minimum of 30 min and a max of 2 h, after collection. The serum was obtained by centrifugation at 1500 g for 15 min at room temperature.…”
Section: Dna Extraction and Grn Tagging Snp Determinationmentioning
confidence: 99%
“…An Italian case-control study with 354 patients and 343 controls assessed whether five SNPs in PGN, a gene implicated in neurodegenerative diseases such as frontotemporal dementia, Alzheimer's disease, and amyotrophic lateral sclerosis, might also be associated with MS. SNP rs2879096 TT genotype trended in an association test with MS phenotype (Fenoglio et al, 2010 …”
Section: Progranulin (Pgn)mentioning
confidence: 98%
“…Stratifying according to gender, an association with rs4792938 C allele and rs2879096 T allele were found in male PPMS patients compared with controls. Haplotype analysis showed that frequency of TC haplotype of rs2879096 and rs4792938 are increased in PPMS male patients compared with male controls 78 . In a separate study, genetic variability across 400 MS patients was analyzed to explore association between GRN genetic variability and MS severity and relapse recovery; two additional single nucleotide polymorphism (SNP) sites, rs9897526 A allele and rs5848 T allele, were associated with a more severe disease course (Multiple Sclerosis Severity Score > 5), and reduced level of PGRN in serum 79 .…”
Section: Multiple Sclerosismentioning
confidence: 96%
“…When comparing GRN gene (coding PGRN) variability between 354 MS and 343 control samples, no significant associations were found. However, after stratifying according to MS subtypes, a significantly increased frequency of the rs2879096 TT genotype was found in primary progressive MS (PPMS) compared with healthy controls 78 . Stratifying according to gender, an association with rs4792938 C allele and rs2879096 T allele were found in male PPMS patients compared with controls.…”
Section: Multiple Sclerosismentioning
confidence: 99%